THE “WILD BEAUTY” OF BRAHMS’S RHAPSODIES, OP. 79. STRUCTURAL ANALYSIS AND COMPARATIVE ANALYSIS OF PERFORMANCES - SHWAN, Sebastian; DRĂGULIN, Stela (Studia Universitatis Babes-Bolyai Musica, 2021)
The present paper focuses on the Two Rhapsodies, Op. 79 which, along with Op. 119 No. 4, form the triad of Brahms’s rhapsodies for piano. Devised according to the ancient notion of the rhapsody, with the development of the epic tension, these works evoke the “Charites and the Heroes”, following the technical and compositional patterns laid out in the piano miniatures in Op. 76, at the same time, recalling the ideas that lay at the basis of the Ballads Op. 10. In the first part of the paper, aspects regarding the analysis of the structure are revealed, the aim of the research being the disclosure of the constituting structure, which will inspire the performing artist to convey and reveal the composer’s intentions. A system of structural ramification has been made, starting from the overall image to the smallest details, represented in tables that contain the following aspects: structure, main structural elements, thematic material, tonal scheme. Within the analysis, the harmonic and rhythmic dimensions will be indicated as well. The second objective of the research concerns three important renditions of pianists Radu Lupu, Martha Argerich, and Murray Perahia – three distinct conceptions regarding the performance, the style, and technique as well. Elements pertaining to the following dimensions will be observed: agogic accents and dynamics, phrasing, tempo, faithfulness towards the score, the identification of attack techniques, touch of the keys, and use of pedals, along with the resulting sonority and the semantic connotations of the sound. Rezumat. „FRUMUSEȚEA SĂLBATICĂ” A RAPSODIILOR BRAHMSIENE, OP. 79 – ANALIZA STRUCTURALĂ ȘI REPERE INTERPRETATIVE COMPARATE. Prezentul articol face referire la Rapsodiile op. 79 care, împreună cu op. 119 nr. 4, fac parte din triada rapsodiilor brahmsiene pentru pian. Concepute în accepțiunea antică a noțiunii de rapsodie, cu dezvoltări ale tensiunii epice, acestea evocă „grațiile și eroii”, urmărind tiparele tehnico-componistice ale Miniaturilor op. 76 și amintind totodată de concepția Baladelor op. 10. În prima parte a articolului sunt prezentate elementele de analiză structurală, scopul acestui demers fiind evidențierea suportului constitutiv pe baza căruia artistul cuprinde și relevă viziunea compozitorului. S-a realizat sistemul de ramificare structurală, de la imaginea de ansamblu, până la cele mai mici detalii, recurgându-se la metoda reprezentării grafice a tabelului, care conține următoarele aspecte: forma, principale unități de structură, material tematic, schema tonală. Se vor puncta în cadrul analizei și valori ale suportului armonic, cât și a fundamentului ritmic. Cel de-al doilea obiectiv al articolului vizează trei interpretări de referință ale pianiștilor Radu Lupu, Martha Argerich, Murray Perahia, trei concepții interpretative distincte ca stil și tehnică. Se vor monitoriza elementele de agogică și dinamică, frazare, tempo, fidelitate față de text, identificarea tehnicilor de atac, tușeu și pedalizare, cât și sonoritățile rezultate, cu conotațiile semantice ale acestora. Cuvinte cheie: Brahms, pian, Rapsodiile op. 79, analiză structurală, interpretări comparate